2016
DOI: 10.1080/21691401.2016.1178133
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel biosensor based on a polypyrrole–dodecylbenzene sulphonate (PPy–DBS) film for the determination of amperometric cholesterol

Abstract: Herein a novel amperometric biosensor based on a conducting polymer with anionic dopant modified electrode was successfully developed for detection of cholesterol. Polypyrrole is deposited on a platinum surface and the sodium dodecylbenzene sulphonate (DBS) ion-doped polypyrrole film was electrochemically prepared by scanning the electrode potential between -0.8 and +0.8 V at a scan rate of 20 mV/s. The present electrochemical biosensor was optimized in terms of working potential, number of cycles, concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…In the final step, cholest‐5‐en‐3‐one, which occurs as an intermediate product, undergoes isomerization and turns into the cholest‐4‐en‐3‐one as the final product 40 . The enzymatic determination of cholesterol with biosensor can be indirectly determined by the reduction or oxidation of H 2 O 2 , which occurs as a reaction product, under the appropriate potential 41 . It should be noted that H 2 O 2 is thermodynamically unstable and its theoretical reduction potential is −0.682 V 42 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the final step, cholest‐5‐en‐3‐one, which occurs as an intermediate product, undergoes isomerization and turns into the cholest‐4‐en‐3‐one as the final product 40 . The enzymatic determination of cholesterol with biosensor can be indirectly determined by the reduction or oxidation of H 2 O 2 , which occurs as a reaction product, under the appropriate potential 41 . It should be noted that H 2 O 2 is thermodynamically unstable and its theoretical reduction potential is −0.682 V 42 .…”
Section: Resultsmentioning
confidence: 99%
“…40 The enzymatic determination of cholesterol with biosensor can be indirectly determined by the reduction or oxidation of H 2 O 2 , which occurs as a reaction product, under the appropriate potential. 41 It should be noted that H 2 O 2 is thermodynamically unstable and its theoretical reduction potential is −0.682 V. 42 It has been reported that H 2 O 2 is reduced at different potential values depending on the surface properties of the designed biosensor electrode. [43][44][45][46][47][48] For an accurate biosensor measurement, the potential value at which the reaction mechanism takes place on the electrode surface should be determined.…”
Section: Applied Potentialmentioning
confidence: 99%
“…Therefore, a direct or indirect electron transfer is caused due to a redox reaction between cholesterol and enzyme. Enzymes are immobilized on functionalized electrodes with different supports based on nanomaterials [35][36][37][38][39][40][41][42][43][44], polymers [45][46][47][48][49], hydrogels and sol-gels [2,[50][51] self-assembly monolayers [52] and other matrixes. Different electrochemical methods are used to monitor electron transfer through which cholesterol can be measured, including amperometry [42,51,[53][54][55], cyclic voltammetry (CV) [56][57][58][59], differential pulse voltammetry (DPV) [60], linear sweep voltammetry (LSV) [61][62], charge transfer (CT) [63], electrochemiluminescence (ECL) [64] and electrochemical impedance spectroscopy (EIS) [65].…”
Section: Enzyme-based Electrochemical Sensor For Cholesterolmentioning
confidence: 99%
“…Polypyrrole (PPy), a functional conducting polymer material, is usually considered to be a p-type material with good thermal and high environmental stability, low oxidation potential, and high conductivity [24]. In recent years, PPy-based nanocomposites with different nanomaterials, such as CNT [25], metal oxide [26], dodecylbenzene sulfonate (DBS) [27], have attracted wide attention for biosensor development owing to their large specific surface areas, high conductivity, and biocompatibility. Singh et al [25] studied a biosensor by using PPy/MWCNT as the mediator for cholesterol sensing.…”
Section: Introductionmentioning
confidence: 99%
“…They also demonstrated that the developed cholesterol biosensor could be easily fabricated, had a rapid response time, and was useful in blood serum sampling. A novel amperometric biosensor based on a conducting polymer and DBS-modified electrode was successfully developed by Ozer et al [27]. ChOx was physically entrapped onto the PPy-DBS film surface; then, the cholesterol concentration was determined by performing an electrochemical detection of the H 2 O 2 generated in the enzymatic reaction of cholesterol.…”
Section: Introductionmentioning
confidence: 99%